Microsurgical Clipping of Tandem Carotid-ophthalmic Aneurysms: Illustrated surgical case and technical details. - Echavarria Demichelis, Mickaela; Costa, Matias; Baldoncini, Matias; Conde, Agustin; Purves, Cynthia; Hernesniemi, Juha (Revista Argentina de Neurocirugía, 2021)
Abstract: Introduction: "Tandem" and"Kissing" and aneurysms are rare entities and represent less than 2.8% of all intracranial aneurysms. Its management can be particularly complex due to the unique anatomical features, the reduced working space between two or more adjacent aneurysm necks, and a potentially increased risk of bleeding from "kissing" the aneurysm walls.Endovascular treatment and surgical clipping are accepted treatment methods, but multiple anatomical and imaging factors must be considered.Case description: a 60-year-old female patient with a diagnosis of 2 incidental aneurysms in the left internal carotid artery. No neurological deficits. On 3D CT angiography she showed two saccular aneurysmal formations emerging from the left carotid-ophthalmic segment. The lesions were not in contact, so we call them "in tandem"  and not "kissing" aneurysms.We opted for surgical clipping of both aneurysms. Endovascular treatment was ruled out due to the presence of multiple important arterial branches such as the superior pituitary, ipsilateral ophthalmic, and posterior communicating arteries at the level of the distal aneurysm. A left pterional craniotomy was performed with transylvian access, left anterior intradural clinoidectomy, and unroofing of the optic canal. Finally, both aneurysms were clipped. The patient was discharged on the third postoperative day without neurological deficits.Conclution: The 3D imaging reconstruction provides us with detailed information on the anatomy of the main vessels, the number of aneurysms, the presence or absence of a cleavage plane between the aneurysmal walls to achieve correct clipping.Keywords: Tandem aneurysms, microsurgical clipping.
Keywords: Tandem aneurysms, microsurgical clipping.